2016
DOI: 10.1007/s11064-016-2020-z
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Toxicity of Copper Oxide Nanoparticles in C6 Glioma Cells

Abstract: Copper oxide nanoparticles (CuO-NPs) are frequently used for many technical applications, but are also known for their cell toxic potential. In order to investigate a potential use of CuO-NPs as a therapeutic drug for glioma treatment, we have investigated the consequences of an application of CuO-NPs on the cellular copper content and cell viability of C6 glioma cells. CuO-NPs were synthesized by a wet-chemical method and were coated with dimercaptosuccinic acid and bovine serum albumin to improve colloidal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 91 publications
5
30
0
Order By: Relevance
“…Our findings are in agreement with previous studies. [13][14][15]28 Although, there is a significant variation in the ability of both particles to alter cell cytotoxicity, the differences in cytotoxicity of each concentration of CuO-NPs is not certain as previously reported for somato sensory neurons of a rat in cell culture. 29 The IC 50 decreased by increasing particle size, however, the decrease was nonsignificant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are in agreement with previous studies. [13][14][15]28 Although, there is a significant variation in the ability of both particles to alter cell cytotoxicity, the differences in cytotoxicity of each concentration of CuO-NPs is not certain as previously reported for somato sensory neurons of a rat in cell culture. 29 The IC 50 decreased by increasing particle size, however, the decrease was nonsignificant.…”
Section: Resultsmentioning
confidence: 99%
“…8 Earlier studies showed potent cytotoxic, genotoxic and toxicological activities of CuNPs and even, toxic effects of various types of nanoparticles in C6 glioma cancer cells. 15,22,25 Thus, we first characterized the synthesized CuO NPs for better interpretation of results. The SEM images and zeta size reconfirmed the 30 and 60 nm sizes of CuO NPs, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al indicated CuO-NPs induced a decrease in viability, migration inhibition, G2/M phase cycle arrest, and especially mitogen-activated protein kinase activation in human keratinocytes and mouse embryonic fibroblasts. 27 The cell viability of CuO-NPs decreased in mouse embryonic fibroblasts (48% at 10 µg/mL), 12 and neuroblastoma (37% at 400 µg/mL) cells, 28 in human lung epithelial (93% at 20 µg/cm 2 and 50% at 15 µg/mL), 29,30 airway epithelial (60% at 80 µg/cm 2 ), 31 alveolar adenocarcinomas epithelial (75% at 11 µg/mL), 32 neuroblastoma (60%-70% at 0.01-10 µM), neuroglioma (25%-60% at 0.01-10 µM), 33 C6 glioblastoma (10-1000 µM), 34 cardiac microvascular endothelial, 15 lymphocytes (50% at 0.04 mM), 35 and colon cancer (50% at 40 µg/ mL)cell lines. 36 Muoth et al reported CuO-NPs caused a decrease in human chorionic gonadotropin release and microtissue viability in a 3D co-culture cell model of placental fibroblasts surrounded by a trophoblast cell.…”
Section: Discussionmentioning
confidence: 99%
“…However, CuO-NPs are rapidly dissolving [23,24] and they release ionic copper even in the absence of cells [25][26][27]. Therefore, the copper ions released from dispersed CuO-NPs have been considered to strongly contribute to the copper toxicity [28,29] and to the antibacterial effects [24] described for CuO-NPs. However, at least for glioma cells evidence has also been provided for a direct contribution of nanoparticulate copper in the cell toxicity observed after application of CuO-NPs [30].…”
Section: Introductionmentioning
confidence: 99%